Pathophysiological to Clinical Aspects of Chronic Suppurative Otitis Media (CSOM): Narrative Literature Review - Rachmat Hidayat (Archives of The Medicine and Case Reports, 2022)
Chronic suppurative Otitis Media (CSOM) is inflammation of the middle ear mucosa and mastoid space that lasts more than 2 months characterized by perforation of the tympanic membrane and continuous or intermittent discharge from the ear canal. Secretion in the form of watery or thick clear or pus. CSOM with cholesteatoma is characterized by a perforation that is located marginally or can be tampered with the bone and often causes dangerous complications. CSOM is still a major health problem, especially in developing countries. The incidence of CSOM cases is estimated at more than 20 million people worldwide. Of these, approximately 5 million patients suffer from chronic otitis media with cholesteatoma, although the overall number of cases of chronic otitis media with cholesteatoma appears to be decreasing. The prevalence of CSOM worldwide is around 65-330 million people with complaints of watery ears, 60% of them (39-200 million) suffer from significant hearing loss. The incidence of chronic otitis media with cholesteatoma is 3 in 100,000 in children and 9.2 in 100,000 adults.